(3GdehXa GdYGe aj bGfhf GdYbhHGJ (B/ s - (3CMeO Wg eMeO Nda Gddgs; (3YeQ GdSYjO QeVGf (B: s; (3eCehf eMeO SdGeg (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1991)
(3JHOC gPg GdQSGdI HGdHGH GdChd Yf PGJjI GdbGfhf GdLfGFj, Ke GdHGH GdKGfj Yf Gdeaghe GdLfGFj GdVjb ddehXa GdYGe, Ke GdHGH GdKGdK Yf Gdeaghe GdLfGFj GdhGSY ddehXa GdYGe, hCNjQG GdHGH GdQGHY Yf ehba Gdabg hGdbVGA ef Gdeaghe GdLfGFj ddehXa GdYGe(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1991.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B440 - 459.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdehXa GdYGes; (3PGJjI GdbGfhf GdLfGFis; (3eHOC GdPGJjIs; (3GdehXa GdaYdjs; (3Gdecdahf HNOeI YGeIs; (3GdJTQjY GdShOGfj s; (3GdJTQjY GdaQfSjs; (3GdJTQjY GdLfGFj GdeUQjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs